Interview with: Judge José Luis Jesus - van Rijn, Michela (Utrecht Journal of International and European Law, 2011)
Judge José Luis Jesus, born 20 September 1950, in Santo Antão, Cape Verde, has been President of the International Tribunal for the Law of the Sea (ITLOS) since October 2008. Merkourios inquired into the every-day functioning of this relatively novel institution. In what way does the Tribunal contribute to the body of sea law? And importantly, does another law of the sea tribunal add to the per- ceived 'fragmentation of international law'?